Microcontroller-based micro-resonator sensor signal detection technique/ Nik Siti Sara Mohamed Ghazali - Mohamed Ghazali, Nik Siti Sara (2012)
Microcontroller-Based Micro-Resonator Sensor Signal Detection Technique was designed to detect small Alternating Current (AC) signal from micro-resonator sensors. This project is an alternative approach to measurement technique to typically done in the laboratory that requires table top equipments such as oscilloscope and function generator. The objective of this project is to design a technique that extracts amplitude and frequency of sensor response using microcontrollers as an alternative approach to Micro Electro Mechanical System (MEMS) application. This project is implemented using two techniques. The first technique is voltage incremental comparison and the second technique is voltage differentiation. The input AC signal data read from sensor will be transmitted to microcontroller and displayed on liquid crystal display (LCD). Resonator response is artificially generated and validated against oscilloscope measurements. As for the result, the first technique is much better from the second technique and able to measure micro-resonator sensor response. It found that amplitude average of percentage accuracy is 94.35% while for frequency average of percentage accuracy is 86.35%.